Insights into the roles and driving forces of CCT3 in human tumors - Ma, Jingang; Song, Ping; Liu, Xinling; Ma, Changgeng; Zheng, Mingzhu; Ren, Xiaomin; Wang, Rui; Liu, Wenshan; Lu, Zhong; Li, Jiaqiu (Frontiers in Pharmacology, 2022)
CCT3 played a key role in many cancers. This study aimed to further explore the characteristics of CCT3 from a pan-cancer perspective and reveal the driving forces for CCT3. By bioinformatic analysis, we found that the mRNA and protein levels of CCT3 were abnormally elevated in most tumor types and were correlated with poor prognosis. Single-cell sequencing data indicated an abnormal increase of CCT3 expression in both malignant cells and multiple immune cells. In the tumor microenvironment, CCT3 expression was negatively relevant with immune cell infiltration and immune checkpoint genes expression. In colon cancer, knockdown of CCT3 inhibited cell proliferation. Gene set enrichment analysis showed that CCT3 may be oncogenic by regulating amino acid metabolism. Furthermore, we predicted sensitive drugs for CCT3 by virtual screening and sensitivity analysis. Many driver genes such as TP53 and KRAS were essential for CCT3 overexpression. Epigenetic factors, enhancers in particular, were also critical for CCT3 expression. Additionally, we constructed the lncRNA/circRNA-miRNA-CCT3 regulatory network. Collectively, CCT3 had the potential to be a diagnostic and prognostic biomarker for multiple tumor types. CCT3 expression was relevant with an immunosuppressive tumor microenvironment. CCT3 could be a new molecular target for colon cancer. Both genetic and epigenetic factors were responsible for CCT3 expression in tumors.